Pengelolaan Kelas Online melalui Penggunaan Google Classroom dan Video Pembelajaran bagi Guru-Guru Sma Negeri 1 Sidikalang - Osco Parmonangan Sijabat; Lisbet Novianti Sihombing; David Berthony Manalu; Susy Alestriani Sibagariang; Esti Marlina Sirait; Novra Melisa Hutabarat; Nurliani Siregar; Ronald Hasibuan; Injen Pardamean Buta-Butar; Herlina Hotmadinar Sianipar; Bangun Munthe; Rianita Simamora (LPPM Universitas Flores, 2021)
The online learning system (in the network) is a learning system without face to face directly between teachers and students but is carried out online using the internet network. Educators must ensure that teaching and learning activities continue to run according to the demands of the curriculum, even though students are at home. With a situation like this, teachers are required to make learning innovations related to the media that will be used to deliver online learning effectively. The diversity of teacher competency levels in carrying out online learning requires socialization activities for online classroom management in terms of using google classroom and making learning videos uploaded to youtube. Seeing these conditions, the service team from HKBP Nommensen University lecturers collaborated with school leaders at SMA Negeri 1 Sidikalang in terms of conducting socialization activities and online classroom management training through the learning media of google classroom and making learning videos uploaded on youtube. The results of the collaboration in the form of community service activities carried out can help teachers at SMA Negeri 1 Sidikalang as evidenced by the average teacher already having online classes and being able to manage online classes through Google Classroom and make good learning videos.